Effect of carbon content on cryogenic mechanical properties of CoCrFeMnNi high entropy alloy. Issue 1 (January 2021) - Semenyuk, A; Klimova, M; Shaysultanov, D; Chernichenko, R; Zherebtsov, S; Stepanov, N
Abstract: The effect of the carbon content (0-2 at.%) on the structure and mechanical properties at room and cryogenic temperatures of CoCrFeNiMn-based high entropy alloys with reduced Cr concentration was studied. The as-cast alloys were cold rolled to a thickness reduction of 80% and annealed at 800°C for 1 hour. As a result, a fully recrystallized microstructure with a grain size of 6.4 μm was produced in the carbon-free alloy. The recrystallized grain size was much smaller (1.5 μm in the alloy with 2.0 at.% of C) due to the pinning effect of the precipitated M23 C6 carbides. The yield strength of the alloys increased with an increase in the carbon concentration from 313 MPa to 636 MPa, while the elongation to fracture slightly decreased from 56% to 43%, respectively, in the alloys with 0 and 2 at.% of C. A decrease in the test temperature to 77K resulted in a significant increase in both the strength and ductility of the alloys. The alloys had high values of impact toughness of 140 J/cm 2 and 85 J/cm 2, respectively, in the alloys with 0 and 2 at.% of C. A decrease in the testing temperature did not have a noticeable effect on the impact toughness.